Analysis of Online Learning Problems on Character Education of Students - Arnaz Anggoro Saputro; Nurhasan Nurhasan; Abdul Rachman Syan Tuasikal (Universitas Negeri Makassar, 2021)
Character education is a manifestation of reaching a generation that is smart and capable of having useful morals and personalities for the Indonesian nation. The success of education is seen from how big their character is when they can balance their cognitive, affective and psychomotor to become the perfect human being. In 2020 there has been a Covid - 19 pandemic which has caused everything to change, learning carried out in schools has changed according to government regulations carried out at home online or learning remotely. The research that is currently being carried out is descriptive qualitative with literature studies that attempt to provide an overview of the solutions to online learning problems to character education for students in junior high schools. This manuscript presents online learning problems, the impact of online learning on character education of students, solutions and problem solving. This research uses literature study / literature study, by examining several research results, articles, ebooks and case studies that occur in the field.